2013
DOI: 10.1371/journal.pone.0079319
|View full text |Cite
|
Sign up to set email alerts
|

Independent and Additive Effects of Glutamic Acid and Methionine on Yeast Longevity

Abstract: It is established that glucose restriction extends yeast chronological and replicative lifespan, but little is known about the influence of amino acids on yeast lifespan, although some amino acids were reported to delay aging in rodents. Here we show that amino acid composition greatly alters yeast chronological lifespan. We found that non-essential amino acids (to yeast) methionine and glutamic acid had the most significant impact on yeast chronological lifespan extension, restriction of methionine and/or inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
65
1
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(78 citation statements)
references
References 55 publications
2
65
1
3
Order By: Relevance
“…All organisms produce ATP by glycolysis through the degradation of glucose. Met or glucose restriction was reported to cause lifespan extension in many eukaryotes (4)(5)(6)(7)(8)(9). Thus, we assumed that consumption of Met and glucose for AdoMet synthesis was required for extended CLS in SSG1-1 and that the CLS of SSG1-1 would be diminished by limiting either the Met or glucose concentration in the medium.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All organisms produce ATP by glycolysis through the degradation of glucose. Met or glucose restriction was reported to cause lifespan extension in many eukaryotes (4)(5)(6)(7)(8)(9). Thus, we assumed that consumption of Met and glucose for AdoMet synthesis was required for extended CLS in SSG1-1 and that the CLS of SSG1-1 would be diminished by limiting either the Met or glucose concentration in the medium.…”
Section: Resultsmentioning
confidence: 99%
“…DR, such as calorie restriction (CR) or Met restriction, extends the lifespan of a wide range of species (4)(5)(6)(7)(8)(9). Although we have knowledge of several metabolites that contribute to the beneficial effects of DR (10)(11)(12), the molecular mechanism underlying the key metabolites responsible for DR regimens is far from complete.…”
mentioning
confidence: 99%
“…Thus, we further explored the individual role of each amino acid on the high-protein toxicity and we found that the over-representation of methionine (Met), serine (Ser), threonine (Thr) and phenylalanine (Phe) were especially harmful. These amino acids when in excess decrease growth and/or lifespan in a wide variety of life forms such as unicellular algae (Met, Thr and Ser [45]), yeasts (Met, Thr and Ser [46][47][48]), roundworms (Phe [49]), flies (Met [50,51]), rodents (Met, Thr, Ser and Phe [46,[52][53][54]), and even cancer tumour cells (Met and Phe [55]) and other human cells (Met [46]). Methionine is proposed to be related to oxidative stress processes [56].…”
Section: Discussionmentioning
confidence: 99%
“…We already know that, certains amino acids regulate life span with greater effects Piper et al, 2014). Methionine restriction extends the life span of yeast (Johnson & Johnson, 2014;Ruckenstuhl et al, 2014;Wu, Song, Liu, & Huang, 2013), flies , mice (Miller et al, 2005), and rats (Orentreich, (Bass, Grandison, et al, 2007;Mair & Dillin, 2008;Metaxakis & Partridge, 2013)). …”
Section: Dr and The Nutrient-sensing Networkmentioning
confidence: 99%